Formative research for a pre-operative psychosocial screening program for cardiac surgical patients: The EMBRACE study, a mixed methods knowledge to action protocol - Susan E. Smith; Marlien Varnfield; David J. Kavanagh; Tricia Rolls; Usha Gurunathan; Bo Janoschka; Karen Hay; Rishendran Naidoo; Jed Duff; Esben Strodl (PLoS ONE, 2025)
Background Psychological comorbidities are common in cardiac surgery patients, however much research on their prevalence, correlates and effects remains subject to methodological inconsistencies, with screening and interventions to address the problem not being systematically applied. More information about patient preferences for support and formative contextual knowledge is needed to improve screening program design, uptake, and benefits. Aims This study aims to estimate the prevalence and relationship of psychosocial comorbidity with cardiac surgery post-operative health outcomes and explore patients’ support interests and preferences in the public hospital acute surgical setting. These findings will generate contextualised knowledge for subsequent development and implementation of a psychosocial screening and support program. Methods A sample of 260 patients will be screened using a pragmatic informatics platform of pre-operatively self-reported psychometric instruments including for depression, anxiety, PTSD, perceived stress, and personality traits. Post-operative outcomes and medical covariates will be linked from routinely collected clinical data as well as post-operative psychometric surveys. Prevalence of exposures of interest will be ascertained, and multivariable regression will assess associations with the primary outcome of Days Alive and Out of Hospital to 30 days (DAOH), controlling for patient-level covariates. Secondary outcomes will include measures of post-operative morbidity, Quality of Life and resource utilisation to 1 year of follow-up. Simultaneously, mixed methods will be used to elucidate patient interests and preferences for available support options including online eMental Health resources in blended care, via a post-operative preferences survey and a nested subsample of semi-structured interviews. Conclusion Inconsistent evidence on screening program implementation and patient benefit necessitates a re-evaluation of locally contextualised evidence. This formative research study design will provide a contextual evidence-base including patient perspectives. This can be used to underpin the collaborative co-design of a multidisciplinary, blended model of care leveraging efficient and cost-effective care services suited to patient preferences.